Farmers' research in practice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Farmers' research in practice: Lessons from the field edited by Laurens van Veldhuizen, Ann Waters-Bayer, Ricarodo Ramírez, Debra Johnson and John Thompson 1997 285pp ISBN 1 85339 392 4